Flattening the curve - London, Martha (Core Library guide to COVID-19., 2021)
Provides a brief history of the COVID-19 disease, explains what it means to "flatten the curve," and details how to do that by washing hands and social distancing. Also discusses how to maintain one's mental health during the pandemic. Includes color photographs, a glossary, sidebars, critical thinking exercises, and online resources.